A Delphi Exploration of Toileting Activity Performance in Individuals With Cerebral Palsy Within the ICF-CY Framework: Unveiling Influential Factors - Azade Riyahi; Malahat Akbarfahimi; Mehdi Rassafiani; Zahra Pournasiri; Maryam Ahmadi; Afsoon Hassani Mehraban (Hindawi-Wiley, 2024)
Conclusion: The study identifies key factors influencing toileting activity performance in individuals with CP. "Main caregiver" emerges as a pivotal factor, followed by neuromusculoskeletal functions, personal factors, attitudes toward menstruation, the toilet environment, and support and relationships.